Speed control of an electromechanical integrated harmonic piezodrive system - Lizhong XU; Yaqi JIANG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2018)
The Authors proposed an electromechanical integrated harmonic piezodrive system. The stability of the output speed of the drive system has important effects on its operating performance. Here, the electromechanical coupled torque equations of the drive system are presented. The transfer function of the speed control system is derived based on the torque equations. The speed fluctuation of the harmonic piezodrive system is analyzed. With a speed feedback controller and a periodic compensated control voltage, the speed fluctuation of the drive system was removed, and the stability and response speed of the control system was improved.